Membangun Website Sekolah MTS Nahdlotul Muslimin menggunakan Framework Codeigniter: Sodiq Aryanto, Yunita Trimarsiah (Universitas Mahakarya Asia, 2021)
Promotion is the most important activity, which plays an active role in informing the benefits of a product. During this time the promotion system at MTs Nahdlotul Muslimin still uses a conventional system (old school system) by distributing brochures and posting bulletin boards at school or with banners. Based on the above case it is necessary to make a website that can help MTs Nahdlotul Muslimin to promote and share information about the services they have widely.Data collection is done by interview, observation, and literature study. The stages carried out in the study are to make a database design, user pages and administrator pages. The database is created using MySQL, the framework uses the CodeIgniterFramework and the Text Edittor Application uses Sublime Text 3.The results of the study are a website Mts Nahdlotul Muslimin School which is located at www.mtsnm-12.com The page contains data about other schools, history, vision and mission, facilities, excellent programs, online registration and the latest student data. On this website there are also pages on how to register new students online, which can be accessed by all groups. Reference : Andi. 2015. PASTI BISA !! Belajar Sendiri CorelDRAW X7. Yogyakarta:Madcoms Madiun. Andi. 2011. Mudah dan Cepat Membuat Website dengan CodeIgniter. Yogyakarta:Wahana Komputer Semarang. Dita Syifani, Ardiansyah Daroes. 2018. Aplikasi Sistem Rekam Medis di Puskesmas Kelurahan Gunung. Volume 9(1):25. Dyah Rhetno Wardhani. 2011. Dukungan Database Dalam Membangun Website Dinamis Yang Interaktif. Volume 4 (1):32-33. Lasmedia Afuan. 2010. Pemanfaatan Framework Codeigniter dalam Pembangunan Sistem Informasi Pendaftaran Laporan Kerja Praktek Mahasiswa Program Studi Teknik Informatika Unsoed. Volume 1 (2):39. Maya Aprilia dan Pujianto. 2017. Sistem Penerimaan Siswa Baru SMKN 2 Baturaja. Volume 8 (1):2. Pradiatiningtyas, Diah, da